1986
DOI: 10.1063/1.336554
|View full text |Cite
|
Sign up to set email alerts
|

Structure and crystal growth of atmospheric and low-pressure chemical-vapor-deposited silicon films

Abstract: Structure and crystal growth of undoped, as-deposited, and annealed silicon films prepared by chemical vapor deposition (CVD) and low-pressure chemical vapor deposition (LPCVD) of silane have been studied with use of x-ray diffraction, Raman spectroscopy, and scanning electron microscopy (SEM). The grain size and a complete texture analysis are performed on CVD films grown at atmospheric pressure and temperature range 600≤Td≤805 °C, LPCVD films grown in the pressure range 0.1≤Pd≤2 Torr and temperature range 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…Therefore, the change in q with increasing [SiF 4 ] may be controlled by the occurrence of h1 1 0i textured grains, though the mechanisms for this are unknown. Changes in strain in a crystalline Si film may also be considered for the control of dominant textures [25,26]. Bisaro et al [26] proposed that h3 1 1i planes are favorably formed as the films were strained.…”
Section: Xrd and Raman Scatteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the change in q with increasing [SiF 4 ] may be controlled by the occurrence of h1 1 0i textured grains, though the mechanisms for this are unknown. Changes in strain in a crystalline Si film may also be considered for the control of dominant textures [25,26]. Bisaro et al [26] proposed that h3 1 1i planes are favorably formed as the films were strained.…”
Section: Xrd and Raman Scatteringmentioning
confidence: 99%
“…Changes in strain in a crystalline Si film may also be considered for the control of dominant textures [25,26]. Bisaro et al [26] proposed that h3 1 1i planes are favorably formed as the films were strained. In the presented work, we observed almost the same tensile stress for the films prepared with [SiF 4 ] = 0 sccm.…”
Section: Xrd and Raman Scatteringmentioning
confidence: 99%
“…The polysilicon films deposited below 580℃ are amorphous whereas those deposited above 600℃ are crystalline in nature. Kamins has observed a similar transition at 600℃ and has suggested that the deposition at this temperature should be avoided in order to obtain reproducible structure [5][6][7][8].For obtaining uniform poly-silicon grains, experiments were made on poly-silicon deposition, doping, annealing. Considering that ion implantation and annealing tend to make poly-silicon grain growing rapidly and it is not easy to control the grain size of the poly-silicon, liquid source was adopted for diffusion doping, which could obtain high concentration and also avoid subsequent annealing process.…”
Section: Experiments Of Uniform Poly-silicon Grainsmentioning
confidence: 99%
“…Starting from amorphous silicon (a-Si) films obtained in the [2][3][4][5] Vd/Vc range (see below), the Vd/Vc decrease leads to the deposition of randomly semi-crystallized silicon (s-Si) due to the polysilicon grains growth during the silicon deposition process. As already shown in figure 8, this volume random crystallization is responsible for tensile stress and therefore for a residual stress increase.…”
Section: Residual Stress Into Silicon Films Deposited From Silane Sihmentioning
confidence: 99%
“…The investigations have mainly concerned the silane SiH4 gaseous source [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. They evidenced that the deposition temperature T, the SiH4 partial pressure P and/or the deposition rate Vd were the main parameters for understanding the silicon films properties: cristallinity, microstructure, roughness, residual stress,… In parallel, the disilane Si2H6 gaseous source was also studied [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%